Individualized concept for the treatment of autosomal recessive polycystic kidney disease with end‐stage renal disease. (3rd March 2020) - Miura, Kenichiro; Sato, Yasuyuki; Yabuuchi, Tomoo; Kaneko, Naoto; Ishizuka, Kiyonobu; Chikamoto, Hiroko; Akioka, Yuko; Nawashiro, Yuri; Hisano, Masataka; Imamura, Hideaki; Miyai, Takayuki; Sakamoto, Seisuke; et al.
Abstract: Management of children with autosomal recessive polycystic kidney disease (ARPKD) who develop end‐stage renal disease (ESRD) remains challenging because of concomitant liver disease. Patients with recurrent cholangitis are candidates for liver‐kidney transplantation, while the treatment for patients with splenomegaly and pancytopenia due to portal hypertension is controversial. Herein, we report 7 children who were treated using an individualized treatment strategy stratified by liver disease. Two patients with recurrent cholangitis underwent sequential liver‐kidney transplantation, while 4 patients with splenomegaly and pancytopenia but without recurrent cholangitis underwent splenectomy followed by isolated kidney transplantation. The remaining patient, who did not have cholangitis and pancytopenia, underwent isolated kidney transplantation. Blood cell counts were normalized after splenectomy was performed at the median age of 8.7 (range, 7.4‐11.7) years. Kidney transplantation was performed at the median age of 8.8 (range, 1.9‐14.7) years in all patients. Overwhelming post‐splenectomy infections and cholangitis did not occur during the median follow‐up period of 6.3 (range, 1.0‐13.2) years. The estimated glomerular filtration rate at the last follow‐up was 53 (range, 35‐107) mL/min/1.73 m 2 . No graft loss occurred. Our individualized treatment strategy stratified by recurrent cholangitis and pancytopenia can be a feasible strategy for children with ARPKD who develop ESRD and warrants further evaluation.